2011
DOI: 10.1088/0953-8984/23/49/496003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cation disorder on structural, magnetic and dielectric properties of La2MnCoO6double perovskite

Abstract: The origin of dielectric anomalies and magnetodielectric response of La2MnCoO6 has been investigated by means of ultra-high resolution synchrotron x-ray powder diffraction, neutron powder diffraction, resistivity, magnetization and dielectric measurements. The study has been performed on two different bulk samples presenting different degrees of Mn/Co order: 95 and 74%. Beside the well-known influence on magnetic properties, our results show that the main effect of disorder lies on the electrical resistivity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
92
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(104 citation statements)
references
References 34 publications
11
92
1
Order By: Relevance
“…Hence, our first attempt was to refine the diffraction data in the cation-ordered P 2 1 /n space group. However, if the cations are ordered in the double perovskite structure, it leads to the appearance of (011) peak in the diffracted intensity [39]. The absence of such a peak in the neutron diffraction data of Ho 2 FeCoO 6 suggested that the degree of ordering is very low in this compound.…”
Section: Neutron Diffractionmentioning
confidence: 98%
“…Hence, our first attempt was to refine the diffraction data in the cation-ordered P 2 1 /n space group. However, if the cations are ordered in the double perovskite structure, it leads to the appearance of (011) peak in the diffracted intensity [39]. The absence of such a peak in the neutron diffraction data of Ho 2 FeCoO 6 suggested that the degree of ordering is very low in this compound.…”
Section: Neutron Diffractionmentioning
confidence: 98%
“…Structural investigations by neutron diffraction has shown that these compounds crystallize into a monoclinic structure with charge ordering of rock salt type (A 2 BB'O 6 ), belonging to the , (#14 or ) 11,12 space group. Within this structure, the cationic ordering state of the B e B' ions, occupying respectively the 2c e 2d Wyckoff sites, has a strong influence on the vibrational, electrical and magnetic properties of the material.…”
Section: Introductionmentioning
confidence: 99%
“…Within this structure, the cationic ordering state of the B e B' ions, occupying respectively the 2c e 2d Wyckoff sites, has a strong influence on the vibrational, electrical and magnetic properties of the material. In particular, the ordering of the magnetic ions (Mn, Co or Ni) in B/B' sites affects the spinphonon coupling 13,14 , the critical magnetic temperatures 15 , the electrical conductivity 12,16 and the dielectric constant 17,18 . Concerning the dielectric constant of LCMO there are some discrepancies on the results presented in the literature: Yáñez-Vilar et al 18 reported that the radio-frequency (<10 4 Hz) dielectric constant of their ceramic samples, at room temperature, increased by two orders of magnitude from the ordered to disordered material, attaining values as high as 10 5 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In situ annealing conditions allow tailoring the oxygen content of the films, therefore controlling their microstructure and magnetic properties. PACS: 75.70.Ak, 81.15.Cd 4 Bulk La 2 CoMnO 6 (LCMO) double perovskite has been the subject of strong interest during the last years [ 1,2,3,4,5,6,7] due to its ferromagnetic insulating character.Besides its perspectives as magnetodielectric material, LCMO is a good candidate for active insulating barriers in spin filters. For these devices, insulating barriers must be thin enough to enable tunneling conduction.…”
mentioning
confidence: 99%